Perancangan Sistem Informasi Akademik SMK TQ Ndholo Kusumo dengan Metode Extreme Programming - Syahid Nur Salas; Adhi Priyanto; Ninik Haryani (LPPM Politeknik Saint Paul Sorong, 2023)
Advancements in information technology have enabled organizations to discover new business strategies that can assist companies, organizations, schools, and governments in facing competition while enhancing productivity. Computer technology and the internet have facilitated information delivery, yet the utilization of Information Technology hasn’t been as effective as possible at SMK TQ Ndholo Kusumo, which still relies on manual systems to support day-to-day operations. This includes administrative tasks related to processing schedule information, teacher data, class data, student data, subject data, and grade data. Consequently, a considerable amount of time is required for these activities. To address these issues, an Academic Information System (AIS) is needed to aid in a more productive and efficient process. This system is designed using extreme programming methods in its development, incorporating unified modeling language for system design, including use case, class, and activity diagrams. System feasibility evaluation is conducted through black-box testing, resulting in a 100% accuracy rate. Therefore, functionally, this system is deemed suitable for use.